1998
DOI: 10.1002/elps.1150191026
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification based on Si‐O and Si‐C sublayers and a series of N‐substituted acrylamide top‐layers for capillary electrophoresis

Abstract: Two approaches were used to prepare a series of surface-modified capillaries. In the first, a sublayer was formed by coupling gamma-methacryloxypropyltrimethoxysilane to the surface silanol groups forming an SI-O bond; a top layer was then formed by polymerizing acrylamide in the capillary, which reacted with the sublayer. In the second approach, a sublayer was formed by silanol chlorination, followed by Grignard coupling of vinylmagnesium bromide to form an Si-C bond at the surface; a top layer was formed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 16 publications
0
76
0
Order By: Relevance
“…If an uncoated or dynamically coated capillary became fouled, or otherwise needed to be cleaned, the following wash procedure was performed at 20 psi: 0.5 M potassium hydroxide for 10 min, 0.5 M hydrochloric acid for 5 min, water for 5 min, and CE (uncoated) or PVA (dynamic) buffer for 5 min. AAP coated capillaries were prepared as described previously [28]. The instrument was aligned using a continuous flow of 10 -9 M fluorescein in CE buffer.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…If an uncoated or dynamically coated capillary became fouled, or otherwise needed to be cleaned, the following wash procedure was performed at 20 psi: 0.5 M potassium hydroxide for 10 min, 0.5 M hydrochloric acid for 5 min, water for 5 min, and CE (uncoated) or PVA (dynamic) buffer for 5 min. AAP coated capillaries were prepared as described previously [28]. The instrument was aligned using a continuous flow of 10 -9 M fluorescein in CE buffer.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…In this experiment, we flush the capillary between runs to remove adsorbed proteins that might interfere with subsequent separations. We have demonstrated that modified acrylamide coatings are useful in reducing protein adsorption during capillary electrophoresis (21). Such coatings will be required for the analysis of highly basic and highly hydrophobic proteins, which were likely lost during our analyses.…”
Section: Discussionmentioning
confidence: 98%
“…Gelfi et al [176] polymerized either acrylic acid (AA), DMA, N-acryloylaminoethoxyethanol (AAEE), or N-acryloylaminopropanol (AAP). A direct Si-C bond at the surface was formed by a silanol chlorination of the surface, followed by a Grignard coupling of a vinylmagnesium bromide [177] to increase resistance of the coating to alkaline hydrolysis.…”
Section: Polymer Brushes By Grafting To Strategymentioning
confidence: 99%